"Breast milk is important": what do nursing mothers in Fortaleza think about breastfeeding? - Lorena Oliveira Peixoto; Daniela Vasconcelos de Azevedo; Leontina Fernandes Britto; Isadora Nogueira Vasconcelos
Abstract Objectives: to analyze the meaning of breastfeeding for nursing mothers, users of the public health network in Fortaleza city, Ceará. Methods: a cross-sectional study was carried out with nursing mothers from nine health units. The data were collected through the application of a socioeconomic and health questionnaire and the Word Free Association Test, using "breastfeeding" as an induced stimulus. The terms referred to in the Word Free Association Test were grouped into categories and analyzed by the EVOC 2000 ®software, which showed the results in a fourcell table, where the categories were distributed according to the level of meaning to the mothers. Results: the sample consisted of 279 nursing mothers. More than 60% of these women referred in receiving guidance on breastfeeding in prenatal, puerperal and childcare consultations, and 68% of them reported having no difficulties in breastfeeding. The most significant categories identified by the Word Free Association Test were: Milk, Important, Health, and Love. Conclusions: for the nursing mothers, breastfeeding is an important practice, represented by the breast milk itself, which is permeated by positive meanings. Knowing these meanings helps to understand the factors associated to early weaning, making it possible to reconstruct care directed to this public.